Extraction of Natural Dye from Phellodendron Amurense and Its Photofading (Journal of Fiber Bioengineering and Informatics, 2018)
Phellodendron amurense was used as natural dye source. Orthogonal experiment was carried out to select\roptimal extract process of phellodendron amurense dye. The orthogonal analysis results showed extract\rtemperature was the most important factor. Stability investigation showed phellodendron amurense\rextract was stable to weak acid and alkaloid environment. Common metal ion had little effects on\rabsorbance of phellodendron amurense extraction. Wool fabric and silk fabric had been dyed with\rphellodendron amurense aqueous solution. Solarization experiment showed high concentration dyeing\rsped up photofading rate and the dyed silk fabric was more sensible to the solarization. Vitamin C acid\rtreatment slowed down photofading rate.